Observations of wave run-up affected by dune scarp during storm conditions: a two dimensional large-scaled movable bed experiment - Lee, Eunju; Van Dang, Hai; Shin, Sungwon; Yoo, Jeseon; Park, Hyoungsu (Frontiers in Marine Science, 2024)
Artificial dunes serve as essential nature-based defenses against the increasing threats posed by climate change and rising sea levels along coastal regions. However, these man-made dunes are particularly susceptible to erosion during severe storm events, necessitating careful consideration of their design for effective coastal protection. Among the myriad factors influencing artificial dune design, wave run-up stands out as a paramount concern. Not only is wave run-up crucial in assessing the extent of coastal flooding, but it also plays a significant role in shaping shoreline dynamics. During intense storm events, wave run-up amplification leads to substantial erosion of sand dunes, forming dune scarps that resemble cliffs. To address these challenges, we conducted a series of innovative two-dimensional large-scale laboratory experiments using movable beds. These experiments aimed to provide a quantitative understanding of wave run-up characteristics on dune scarps. Additionally, our study explored the feasibility of using existing empirical formulas to predict the 2% exceedance of wave run-up (referred to as R2%) in such scenarios. Our results revealed a consistent trend in R2% values, irrespective of variations in the surf similarity parameter when wave run-up was influenced by a dune scarp. Notably, our findings recommend the adoption of the Stockdon empirical formula, incorporating beach slope from the still water level to the dune scarp toe, as an effective method for predicting R2% during highly erosive conditions. This approach can significantly enhance the design and functionality of artificial dunes, bolstering their capacity to safeguard coastal areas from the impacts of severe storms and erosion, thus contributing to resilient coastal ecosystems and sustainable coastal management.